8. CITIZENS PREFERENCES KAJIAN KEBIJAKAN KESEHATAN DI KABUPATEN SEMARANG - Moh. Adnan (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Health development, which is to elevate the healthcare is the first attention of the direction of Semarang regency’s 2010-2015 regional development. In the climate of democracy, the government is not only obliged to create good policies, but also policies that involve the society in the process. One of the form of public involvement is the policy based on citizens’ preferences. The authority on health affair implementation is unconditionally without exception. Semarang regency is dealing with a number of health problem; maternal mortality, infant mortality rate, malnourished toddler, lungs condition, water sanitation, HIV/AIDS, and the implementation of public healthcare problems are among others. Therefore the application of citizens’ preferences based policy is crucial. Various health programs has been implemented such as childbirth insurance (Jampersal), M3 program (Mother Maternity Meeting), and regional health insurance (Jamkesda). Nevertheless, the numerous health affair development planning mechanism has yet still not implemented citizens’ preferences. The public has not been given the alternatives for program and activity offered to solve the health problems.